Nonlinear mixed-state longitudinal and transverse resistivities of superconductors with anisotropic pinning- a phenomenological approach - Shklovskij, Valerij A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
In the presence of anisotropic pinning due to unidirected twins, the nonlinear vortex dynamics is discussed in terms of phenomenologically introduced anisotropic drag and pinning viscosities. The theoretical basis for experimental reconstruction of these viscosities is proposed. The nonlinear Ohm`s law is derived. Assuming the anisotropic pinning alone (a-pinning model): a) new scaling relations for the anisotropic Hall conductivity are predicted; b) nonlinear guiding effects are discussed; c) specific current and angular behavior of current-voltage characteristics are analyzed.